Effects of functional oil blend on performance, blood metabolites, organ biometry and intestinal morphometry in nursery piglets - Gleicianny de Brito Santos; Jansller Luiz Genova; Arlene dos Santos Lima; Aparecida da Costa Oliveira; Franz Dias Gois; Heloíse Trautenmüller; Adriana Bulcão Bock de Faria; Josiane Karine Berwaldt; Sthefany Caroline Marques Viana; Paulo Levi de Oliveira Carvalho (Semina: Ciências Agrárias, 2023)
This study was conducted to assess the effects of functional oil (FO) blend on performance, blood metabolites, organ biometry and intestinal morphometry in piglets. A total of 128 crossbreed piglets (Landrace × Large White, 64 uncastrated males and 64 females, 21 d of age, and 6.79 ± 1.76 kg BW) were allocated in a randomized complete block design with two dietary treatments: a FO-free (FOF) diet or a diet based on added FO (1,500 mg/kg of diet with castor oil plus cashew nutshell oil). Piglets fed FO showed higher (p ≤ 0.05) average daily feed intake, daily body weight gain and final body weight after 23 d of study. For the total period, piglets fed FO showed greater (p = 0.007) feed conversion ratio. On d 23, higher serum total protein (p = 0.026) and globulin (p = 0.050) concentration, lower liver (p = 0.042) and stomach (p = 0.074) weight, and greater (p = 0.082) villi height (VH) in duodenum were observed in piglets fed FO. Nonetheless, piglets fed FOF showed greater (p = 0.054) ileal VH, but greater (p = 0.004) crypt depth (CD) in jejunum. Piglets fed FO showed higher VH to CD ratio in jejunum (p = 0.068) and duodenum (p = 0.074) on d 23 and 37, respectively. Based on the results, FO blend improved the performance of weaned piglets; however, it negatively affected the feed conversion ratio in the total period. Moreover, FO blend promoted changes in total protein concentrations and improvements in digestive and absorptive capacity assessed through VH to CD ratio, with a significant reduction in organs.